The Customer Engagement Effect on Customer Loyalty (Case Study: Marketplace Retailer) - Widya Lelisa Army; Arif Nugroho; Sri Anita; Siti Sarah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research aims to determine the effect of customer involvement on customer loyalty in marketplace retailers. This research uses quantitative methods using data collected through questionnaires from marketplace consumers. Using sequential equation modelling (SEM), the data set was analyzed to observe the significance of the relationship to see the role of customer engagement on customer loyalty. This research is included in explanatory research using a sample of 104 respondents taken from the consumer population of marketplace users. Sampling used a purposive sampling technique with sample characteristics such as age, occupation, and income. The test tools used to test this research instrument were validity tests, reliability tests and classic assumption tests. Hypothesis testing is carried out using the t-test. The results of the research show that there is an influence of customer engagement on customer loyalty, proven by a significance value of <0.01, which is smaller than the alpha value of 0.05. This research highlights the importance of customer involvement to increase customer loyalty as proven by research results of 67.6% of variable X affecting variable Y, where Customer Engagement has a positive influence on Customer Loyalty. Keywords: Customer, Engagement, Loyalty, Effect, Marketplace Retailer